Redox mediators for thermoelectrochemical cells and electroanalysis of quinones in protic ionic liquids - Greatorex-Davies, Peter (2022)
Thermoelectrochemical cells offer promising prospects for future harvesting of waste heat in many areas, such as; power stations, geothermal energy and in devices utilising human body heat. There are two main sets of devices currently used in these areas. The most widely used devices are solid-state thermoelectric cells, but these suffer from low Seebeck coefficients, expensiveness of parts and lack of flexibility. Thermoelectrochemical devices utilising aqueous electrolytes are also used, however, under normal conditions these are limited to operating temperatures below 75°C.